ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Elsinta Mawo Naga; L.G.P. Sri Eka Jayanti; Gede Sanjaya Adi Putra (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2026)
This study will look at how the stock returns of manufacturing companies listed on the Indonesian stock exchange between 2019 and 2023 are affected by the current ratio, loan-to-equity ratio, return on equity, and return on assets. Investors can calculate their gains or losses using the stock return. Sixty deliberate samples and secondary data were used in this quantitative analysis. The Indonesian stock market's annual financial statement provided the secondary data used in this study. Multiple linear regression analysis was used by researchers to look into it. Based on the available data, stock returns are negatively impacted by the debt-to-equity ratio, but positively by the current ratio, return on equity, and return on assets. At the same time, stock performance is affected by changes in the debt to equity (DER), return on equity (ROE), return on assets (ROA), and current ratio (CR).